Regional preparedness for mass acetylcholinesterase inhibitor poisoning through plans for stockpiling and interhospital sharing of pralidoxime - Broach, MD, MPH, MBA, FACEP, John; Krupa, BS, Robert; Bird, MD, FACEP, FACMT, Steven B.; Manuell, MA, MD, FACEP, Mary-Elise (American Journal of Disaster Medicine, 2014)
Background: Regional preparedness efforts related to the stockpiling and interhospital sharing of critical antidotal medications is an important topic in the age of terrorism and weapons of mass destruction. Little attention has been paid to how well regional preparedness efforts specifically affect availability of pralidoxime (2-PAM) if it were needed to treat a mass poisoning with acetylcholinesterase inhibitors (organophosphorus pesticides or nerve agents). Objectives: The authors sought to assess whether hospitals in one region of Massachusetts (Department of Public Health Region 2, Central Massachusetts) have adequate plans for responding to a large number of patients requiring 2-PAM as might occur after the intentional release of nerve agents or organophosphorus chemicals into a civilian population or the food or water supply. Methods: The Massachusetts DPH Region 2 contains 10 acute care hospitals including one level 1 Trauma Center that is also the only tertiary care hospital in the region. A 13-question online survey was used to assess three important components of 2-PAM availability: 1) the amount of 2-PAM available, 2) regional medication sharing activities, and 3) attitudes and awareness of resources available in the Strategic National Stockpile (SNS). Results: Seven of 10 hospitals participated in the survey (response rate 70 percent). Of these seven hospitals, only 2 (28.5 percent) had any 2-PAM on hand (4 and 6 g). Despite the existence of a region-wide memorandum of understanding that includes medication sharing, only two hospitals’ responses included awareness of this agreement. Two hospitals had considered the problem of inadequate 2-PAM supplies before receiving the survey. Five of 7 (71.4 percent) hospitals would consider accessing the SNS if the need for antidotes were exceeded by their own supply. Conclusion: Recognition of regional planning for sharing of antidotes such as 2-PAM is lacking in the surveyed region and could lead to inability to care for large number of patients affected by an intentional or accidental large-scale release of acetylcholinesterase inhibitors.